Effects Of Oestrus Synchronization Protocols And Artificial Insemination Techniques On Conception Rates Of Boer Crossbred Does In Malaysia - Obad Hezam, Nasser Saleh (2008)

(untitled)
A total of 83 Boer crossbred does weight between 14 - 44 kg were randomly selected and allocated into 2 groups. The first group of does (34) were divided into two subgroups: Group A (n = 21 does) and Group B (n = 13 does). All does in Group A (GA) were synchronized using CIDR containing 0.3 g progesterone for 17 days and injection of 50 μg PGF2α and 250 IU of eCG at CIDR removal. Does in Group B (GB) were synchronized using CIDR containing 0.3 g progesterone for 17 days and injection of 50 μg PGF2α without eCG at CIDR removal. All does in GA and GB were naturally mated using two bucks. Oestrus response, time and number of mating were recorded at 24-72h after CIDR removal. The does were observed twice daily at 7 am and 5 pm for two hours for three days. In the second group, 49 does were allocated into three subgroups G1 (n=20), G2 (n=14) and G3 (n= 15). All does were synchronized using CIDR for 17 days. At CIDR removal all does were injected intramuscularly with 50 μg PGF2α and different doses of 100, 200 and 250 IU of eCG for G1, G2 and G3 respectively. At 48-56 h after CIDR removal all does were inseminated with 0.25 ml frozen semen contains 25 ×106 sperm/straw by different artificial insemination techniques using the transcervical (TC), intracervical (IC), intravagina (IV), or intrauterine (IU). Result of the study showed that oestrus responses were 100 % and 53.85 % for GA (CIDR with eCG) and GB (CIDR without eCG) respectively. There were significant difference (p<0.05) in oestrus responses between the two groups. Shortest oestrus responses were observed in GA, followed by GB. Conception rates for the groups GA and GB were 24% (5/21) and 38.5% (5/13) respectively. There were significant difference (p<0.05) in the conception rates of GA and GB. Conception rates using four AI techniques were 0% for G1 and G2. In G3 the conception rate were 40%, 25%, 0% and 0% following TC, IC, IV and IU AI techniques respectively. There were significant difference (p<0.05) in the conception rate among the three groups with different concentration of eCG, there were no significant difference in the conception rate among the different methods of AI used in all groups. For group G3 the conception rates by artificial insemination technique using TC is better than the IC, IV and IU techniques. This study suggested that the synchronization protocol of CIDR with eCG for 17 days were found better than CIDR without eCG. TC technique is preferred than IU using frozen semen in crossbred Boer does that were synchronized using CIDR for 17 days and injected with 250 IU of eCG and 50 μg PGF2α at CIDR removal.